First-principles study of the electronic structure and elastic properties of SrGa2 under pressure. (September 2021) - Parlak, Cihan
Abstract: Determination of detailed electronic and lattice dynamical properties of hexagonal SrGa2 binary system under external pressure with the aid of first-principles calculation methods is of great importance in terms of the basic characteristics of binary system. On this basis, the phonon dispersion curves are calculated by the high-symmetry directions and related phonon frequencies parameters at the Brillouin zone center using density functional perturbation theory when the elastic constants are computed through the metric-tensor formulation. Besides, the fundamental quantities such as the electronic band structures, Fermi surface topologies, and detailed phonon dispersions are sensitively examined. At the same time, it is examined whether there is a close relationship between the determined properties and superconducting properties of SrGa2 material. However, the calculations clearly show that the information obtained directly from the electronic band structure and Fermi surfaces is insufficient to explain the superconductivity phenomenon of such materials.